Breaking barriers: Scientific contributions in virology from women in low- and middle-income countries - Chinunga, Tehillah Taonga; Titanji, Boghuma Kabisen; Chahroudi, Ann (Frontiers in Virology, 2023)
The advancement of science has been a collective effort and benefits from a diversity of views and gender representation. However, support for and recognition of women in science is often insufficient. Despite historically being marginalized by the scientific community, research by women has advanced the field of virology, from the discovery of rotavirus and HIV to a vaccine for polio and the initial description of a virus’ ability to cause cancer (1-6). Although women in STEM are continuing to share their diverse wealth of knowledge and innovation, even today many are under-recognized and under-supported in low- and middle-income countries (LMICs). This review will highlight women in virology from LMICs in Africa, Asia, and Latin America where the barriers to scientific education and achievement for women can be far greater than in high income countries. Despite these barriers, the women we profile below have made important contributions to translational virology. We hope this review will contribute to the global expansion of efforts to provide improved access to and retention in scientific careers for women.